THE EFFECTS OF ROOMING-IN CARE TO SUCCESSFUL BREASTFEEDING: A LITERATURE REVIEW - Anita Setyawati; Restuning Widiasih; Ermiati . (Journal of Maternity Care and Reproductive Health, 2018)
Providing breast milk for a newborn is one method to reduce baby morbidity and mortality. "Baby-Friendly Hospital Initiative (BFHI)" is a program to support the practice of breastfeeding newborns in hospitals, one of them is by rooming in care, however not all hospitals do rooming-in care, including in Indonesia,  and information about the effectiveness of rooming into successful breastfeeding is limited. This literature review was conducted to identify the effectiveness of rooming-in to encourage successful breastfeeding. The databases were CINAHL, and PubMed with keywords: breastfeeding, post-partum, baby, and rooming-in. There were eight articles that appropriate with the inclusion criteria. The results found that four of the six articles showed the effect a rooming-in on success breastfeeding, but two articles showed that there was no rooming-in effect on breastfeeding. Factors that influence the results of these studies include respondent demographic characteristics, health workers, family factor, and respondent's self-efficacy. Further research is needed specifically to examine the effectiveness of baby friendly hospital programs in Indonesia to breastfeeding management and to explore deeply about breastfeeding failure in rooming-in services.Keywords: Baby, breastfeeding, mother, rooming-in, post-partum.